Using high hydrostatic pressure as an abiotic elicitor strategy for improving capsaicin production in free and immobilized cell suspension cultures of Capsicum annuum L. - İşlek, Cemil; Koç, Esra; Altuner, Ergin Murat; Alpas, Hami (Informa UK Limited, 2021)
In this study, the effects of immobilization and high hydrostatic pressure (HHP) on capsaicin production in cell suspension culture of pepper seeds at different application times were investigated....
Keywords: Capsicum annuum; elicitor; high hydrostatic pressure (HHP); immobilization; capsaicin